Cardiovascular biomarkers for risk stratification in primary prevention - Neumann, Johannes T; de Lemos, James A; Apple, Fred S; Leong, Darryl P (European heart journal, 2025)
The foundation of preventive cardiology relies on the assessment of cardiovascular (CV) risk using scores based on traditional risk factors. However, risk models based on these risk factors provide only moderate discrimination and some are poorly calibrated, highlighting a need for improved approaches to risk assessment. Cardiovascular biomarkers, including cardiac troponins, natriuretic peptides, and inflammatory markers, can be used to reclassify CV risk, especially in individuals at intermediate risk, providing opportunities for optimization of primary prevention strategies. This review provides an overview of the characteristics of a circulating biomarker that would promote its clinical use and on the existing evidence behind CV biomarkers for risk stratification. Hundreds of studies have described robust associations between CV biomarkers and incident CV events. However, the incremental value, when biomarkers were added to conventional risk factor models, has generally been modest in terms of improvement in model performance. The review also describes emerging proteomic techniques that enable high-throughput analysis of circulating proteins, presenting opportunities for improved CV risk prediction. Despite encouraging findings, challenges remain in integrating these biomarkers into clinical practice, and there is a need for evidence from clinical trials to demonstrate their cost-effective impact on reducing CV events. While biomarkers hold promise for enhancing CV prevention strategies, their routine application in clinical settings requires further innovation and investigation to establish clear treatment guidelines and optimize patient outcomes.